Contribution to the knowledge of Green lacewings of Croatia (Insecta: Neuropterida: Chrysopidae) - Thierry, Dominique (Acta entomologica slovenica (Ljubljana), 2015)
We collected green lacewings in western Croatia by sweeping trees and edges, both at sea level and in more or less mountainous districts. Amongst the 11 occurring identified species, four are new to the Croatian fauna: Nineta carinthiaca (Hölzel, 1965) registered near the Lokve Lake, in the county of Gorski Kotar, Pseudomallada ventralis (Curtis, 1834) collected near Jezerce in the Plitvice National Park, Ps. inornatus (Navás, 1901) near Breze in Gorski Kotar and Ps. venustus (Hölzel, 1974) near Pirovac and Vrsine on the Dalmatian coast.
Keywords: Chrysopidae; Croatia; Hrvaška; lacewings; Neuropterida; Nineta carinthiaca; Pseudomallada; tenčičarice